2013
DOI: 10.1016/j.chemosphere.2013.04.061
|View full text |Cite
|
Sign up to set email alerts
|

The time- and age-dependent effects of the juvenile hormone analog pesticide, pyriproxyfen on Daphnia magna reproduction

Abstract: Pyriproxyfen is an insecticidal juvenile hormone analog that perturbs insect and tick development. Pyriproxyfen also alters parthenogenic reproduction in non-target cladoceran species as it induces male production that can lead to a decrease in fecundity, a reduction in population density, and subsequent ecological effects. In this study, we investigate the impacts of pyriproxyfen on Daphnia magna reproduction using a series of male production screening assays. These assays demonstrate that pyriproxyfen increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 36 publications
2
35
0
Order By: Relevance
“…Nevertheless, some differences between MF-induced and naturally produced males have been described. For example, MF-induced males show delayed development and decreased fecundity (Olmstead and LeBlanc 2002; Tatarazako et al 2003; Ginjupalli and Baldwin 2013). We could also observe this in a preliminary study on our own D. galeata populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, some differences between MF-induced and naturally produced males have been described. For example, MF-induced males show delayed development and decreased fecundity (Olmstead and LeBlanc 2002; Tatarazako et al 2003; Ginjupalli and Baldwin 2013). We could also observe this in a preliminary study on our own D. galeata populations.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the NMDA receptor seems to be involved in signaling upstream of MF and may be a sensor of environmental stimuli (LeBlanc and Medlock 2015; Toyota, Miyakawa, Yamaguchi, et al 2015). In addition, exogenous treatment with MF and other JH III analogs induces male production in a dose-dependent manner (Olmstead and LeBlanc 2002; Tatarazako et al 2003; Ginjupalli and Baldwin 2013). Some of these JH III analogs are common insecticides that reach freshwater systems with rain washout, where they can disturb the natural cycles of sexual and asexual reproduction in Daphnia .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The juvenoid analog pyriproxyfen is used in agriculture as a growth regulator to inhibit the larval development and maturation of many arachnid and insect pests: ticks, mosquitos, ants, houseflies, and fleas (Sullivan and Goh, 2008). This molecule also affects crustaceans, inducing morphological abnormalities and limiting growth rates in decapods (LeBlanc, 2007), decreasing female fecundity and altering the sex ratio in branchiopods (Olmstead and LeBlanc, 2003;Ginjupalli and Baldwin, 2013), and reducing sperm production in amphipods (Trapp et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…PPF is a juvenile hormone analogue (JHA) that interrupts normal development and metamorphosis of targeted mosquitoes [11]. It also alters parthenogenic reproduction in non-target cladoceran species as it induces male production that can lead to a decrease in fecundity, a reduction in population density, and subsequent ecological effects [12]. Highly potent in terms of activity and specificity, PPF degrades rapidly in soil under aerobic conditions, with a half-life of 6.4-36 days and it disappeared from aerobic lake water-sediment systems with half-lives ranging from 16 to 21 days.…”
Section: Introductionmentioning
confidence: 99%